Characteristics of patients with infective endocarditis and no underlying cardiac conditions. Issue 9 (2nd September 2022) - Radjabaly Mandjee, Aleyya; Filippetti, Laura; Goehringer, François; Duval, Xavier; Botelho-Nevers, Elisabeth; Tribouilloy, Christophe; Huguet, Raphaëlle; Chirouze, Catherine; Erpelding, Marie-Line; Hoen, Bruno; Selton-Suty, Christine; Agrinier, Nelly; et al.
Abstract: Background: Infective endocarditis (IE) typically occurs in patients with underlying cardiac conditions (UCC). Little is known about IE in patients without UCC. We aimed to describe the clinical, microbiological and imaging characteristics, management, and in-hospital mortality of IE patients without UCC. Methods: We analysed the data of patients with definite IE included in an observatory between 1st January 2009 and 31st December 2019. We described patients without UCC compared to those with UCC. Results: Of 1502 IE patients, 475 (31.6%) had no UCC. They were younger (median 64.0 [19.0–101.0] vs. 70.0 [18.0–104.0] years, p < .001), more often on chronic haemodialysis (5.5% vs. 2.7%, p = .008), and had more often malignancy (22.5% vs. 17.3%, p = .017), immune deficiency (10.3% vs. 6.4%, p = .008), and an indwelling central venous line (14.5% vs. 7.0%, p < .001). They more often developed cerebral complications (34.7% vs. 27.5%, p = .004) and extracerebral embolism (48.6% vs. 36.1%, p < .001). Causative microorganisms were less often coagulase negative staphylococci (5.9% vs. 10.8%, p = .002) or enterococci (10.3% vs. 15.0%, p = .014) and more often group D streptococci (14.1% vs. 10.0%, p = .020). Vegetations were more common (92.8% vs. 77.0%, p < .001) and larger (14.0 [1.0–87.0], vs. 12.0 [0.5–60.0] mm, p = .002). They had more valve perforation or valve regurgitation (67.4% vs. 53.0%, p < .001) and underwent valve surgery more often (53.5% vs. 36.3%, p < .001). In-hospital mortality did not significantly differ between groups. Conclusion: Patients with IE and no UCC were younger than those with UCC, had specific comorbidities and portals of entry, and a more severe disease course.